Respuesta :

Answer:

12

Step-by-step explanation:

(whole secant) x (external part) = (tangent)^2

PC * PA = PB^2

(PA+AC) * PA = PB^2

(4+32) * 4 = PB^2

36*4 = PB^2

144 = PB^2

Taking the square root of each side

sqrt(144) = sqrt(PB^2)

12= PB

Answer:

a

Step-by-step explanation:

Given a tangent and a secant to a circle from an external point, then

The square of the tangent is equal to the product of the external part and the whole of the secant , that is

PB² = PA × PC = 4(4 + 32) = 4 × 36 = 144 ( take square root of both sides )

PB = [tex]\sqrt{144}[/tex] = 12 → a